Optical bistability in reflection from a multilayer metal-dielectric structure with Kerr nonlinearity - Ilchenko, S.G.; Lymarenko, R.A.; Taranenko, V.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
Both static and dynamic characteristics of light reflected from a specially designed multilayer metal-dielectric structure with Kerr nonlinearity have been studied in this work. Various regimes of nonlinear reflection from the structure have been demonstrated, including bistable switching between low and high reflection states, which occurs at low intensity of the incident light due to a significant enhancement in the optical field in the nonlinear layer under conditions of total internal reflection. This nonlinear structure has been proposed to be used as an optically controlled intracavity laser modulator. Досліджено як статичні, так і динамічні характеристики світла, відбитого від спеціально розробленої багатошарової метал-діелектричної структури з нелінійністю Керра. Продемонстровано різні режими нелінійного відбивання від структури, включаючи бістабільне перемикання між низьким і високим станами відбивання, яке відбувається при низькій інтенсивності падаючого світла завдяки значному підсиленню оптичного поля в нелінійному шарі в умовах повного внутрішнього відбивання. Запропоновано використовувати цю нелінійну структуру як оптично керований внутрішньорезонаторний лазерний модулятор.